(3GdZdh aj GdJHOjY (B:s (3ehGba hBKGQ (B/s - (3Hf CMeO, YHO GdQRGb Hf YHO Gddgs ((3GdLgQGA (B- (3GdchjJ (B:s (3OGQ EjdGa GdOhdjI ddfTQ hGdJhRjY ,s, 2016)
(3jJfGhd cJGH (B((3GdZdh aj GdJHOjY ehGba hBKGQ(B) (3hGdPj bGe HJCdjag (B((3YHO GdQRGb Hf YHO Gddg Hf CMeO(B) (3ehVhY (B((3GdHOY aj GdESdGe(B) (3hGdOYhI aj HOGjI GdbQf GdNGeS YTQ GdgLQj hCSHGH GdaQbI hGdNdGaGJ hehba GdYdeGA efgG hjJMOK Yf HYV GdaJf GdJj MUdJ eY GdSdajjf ef CLd gPG GdZdh(B.s
Keywords: (3hYX hEQTGOs; (3GdZdhs; (3GdHOYs